The Implementation of SDGs Program on Liquid Waste Processing for the Pasteurized Milk Industry - Eva Tiara Khullah Mahaya; Ihlasul Amalia; Lutfita Aisyatul Wafiroh; Shofia Rohana Zulfa; Marwa Fajrin (PT FORMOSA CENDEKIA GLOBAL, 2023)
The SDGs (Sustainable Development Goals) program is the result of an agreement between nations in the United Nations (United Nations) which is very important to save nature. This study aims to discuss in more depth the implementation of the SDGs program in the wastewater treatment of the pasteurized milk industry. The type of research used is field research supported by a study of literature with a qualitative approach. The main data collection technique in this study was through field visits, observations, interviews, and documentation supported by searching for materials in the form of articles, journals, scientific papers, theses, final assignments, or books related to case studies to draw conclusions and develop theoretical aspects. and aspects of practical benefits. The results of the study show that the implementation of the Sustainable Development Goals (SDGs) program in the processing of wastewater from the pasteurized milk industry can be in the form of reducing pollution of the proportion of liquid waste and minimizing the release of hazardous materials or materials by recycling significant liquid waste and reusing the recycled liquid waste as a whole and safe and global.